The Emperor's new groove - Fullmer, Randy; Dindal, Mark.; Williams, Chris, 1971-; Reynolds, David (Dave); Spade, David; Goodman, John, 1952-; Kitt, Eartha; Warburton, Patrick; Malick, Wendie; Sting (Musician); Hartley, David (Composer); Debney, John.; et al. ([United States] : Walt Disney Home Entertainment ; Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2005)
The emperor is turned into a llama by his ex-administrator and must regain his throne with the help of a llama herder. Includes never-before-seen footage and a sneek peak at Kronk's New Groove.
Title from container.
Originally released as a motion picture in 2000.
Special features: deleted scenes; The Emperor's got game; Rascal Flatts music video; Sting's Making the Music video; behind the scenes; audio commentary with the filmmakers ; sneak peek of the all-new Kronk's New Groove.
Lyrics by Sting ; music by Sting and David Hartley ; score composed and conducted by John Debney ; art director, Colin Stimpson ; editor, Pamela Ziegenhagen-Shefland.
Voices, David Spade, John Goodman, Eartha Kitt, Patrick Warburton, Wendie Malick.
MPAA rating: G.
Keywords: Emperors -- Juvenile drama; Llamas -- Juvenile drama; Children's films; Video recordings for the hearing impaired